'We are creating a reality': teacher agency in early bilingual education. Issue 3 (2nd September 2018) - Dubiner, Deborah; Deeb, Inas; Schwartz, Mila
ABSTRACT: This study was conducted within the context of bilingual Arabic-Hebrew medium preschools in Israel which were established to incorporate instruction in the native languages of both majority and minority children in the classroom. Bilingual education in various settings produces a wide variety of outcomes in terms of language proficiency, cultural awareness, and scholastic achievement. The purpose of the present study was to examine teacher agency in changing the language model of the preschool that aimed at enhancing willingness to use L2 (Arabic) among the Hebrew-speaking 4–6-year-old children. Two research questions guided this study: 1) How did teachers implement their agency in the process of language model modification; and 2) Is there a correspondence between teachers' perception of their role in the process and the observed language practices in the preschool? To answer these questions, we used multiple sources of qualitative data, such as observations and interviews. The findings indicate that teachers saw themselves as agents of linguistic change and were adamant about providing the class with maximum exposure to Arabic during the designated period of the project. Secondly, teachers made use of several strategies aimed at enhancing Arabic L2 output amongst Hebrew-speaking children who were previously reluctant to use the language. Finally, there is a clear correspondence between teachers' and researchers' perception of the former's agency in the modification of the language model. The findings are discussed from the perspective of strategic and critical pedagogies.